Polyethylene glycol: An effective agent for isocyanate-based polyimide foams with enhanced foaming behavior and flexibility. (September 2019) - Tian, Huafeng; Yao, Yuanyuan; Liu, Weilin; Wang, Kai; Fu, Liwei; Xiang, Aimin
A series of polyimide foam materials were prepared via one-step process, and the effect of polyethylene glycol on the morphology and properties of the foams was investigated. The results showed that the mean cellular diameter increased from 0.49 to 0.57 mm with the increase of polyethylene glycol content. Meanwhile, with the addition of polyethylene glycol, the tensile strength of polyimide foams increased from 18 to 23 kPa. It was proved that the foaming behavior and flexibility of polyimide foams were greatly improved due to the introduction of polyethylene glycol. As a kind of chain extender, polyethylene glycol reacted with isocyanate to form the flexible urethane segment, which improved the flexibility of polyimide molecular chain and promoted foaming behavior. In addition, all the foams exhibited fine thermal stability with temperature at 5% weight loss of about 350°C. The limiting oxygen index values of the prepared polyimide foams decreased with the increase of polyethylene glycol content, while the heat release rate increased, indicating certain decrease of the flame retardant properties. However, the fine cell structure can still be observed under the residual carbon structure after the burning, indicating fine flame retardancy.